Acute Cardiac Events in Patients With Severe Limb Infection. (December 2018) - Singh, Mohita; Khan, Khurrum; Fisch, Evan; Frey, Christopher; Mathias, Kristen; Jneid, Hani; Musher, Daniel M.; Barshes, Neal R.
Recent studies have shown an association between infections, such as influenza, pneumonia, or bacteremia, and acute cardiac events. We studied the association between foot infection and myocardial infarction, arrhythmia, and/or congestive heart failure. We analyzed the records of 318 consecutive episodes of deep soft tissue infection, gangrene, and/or osteomyelitis in 274 patients referred to a vascular surgery service at a tertiary center. We identified 24 acute cardiac events in 21 of 318 (6.6%) episodes of foot infection or foot gangrene. These 24 events included 11 new myocardial infarctions (3.5%), 8 episodes of new onset or worsening congestive heart failure (2.5%), and 5 new arrhythmias (1.6%). Tachycardia and systemic inflammatory response syndrome were associated with acute cardiac events ( P < .05 for each). The 1-year survival of patients with acute cardiac events was 50.4%, significantly lower than the 91.7% 1-year survival of patients without acute cardiac events ( P < .0015). Acute cardiac complications are not uncommon among patients presenting with severe foot infection and are associated with a high 1-year mortality. Primary care physicians, cardiologists, and vascular and orthopedic surgeons must keep a high index of suspicion for the occurrence of an acute cardiac event.